Kitty and the sky garden adventure - Harrison, Paula (Harrison, Paula. Kitty, 2020)
Kitty is a superhero-in-training with feline superpowers. She dreams of being like her superhero mum one day, but she's still got a lot to learn. Join Kitty and her cat crew for a series of enchanting adventures by the light of the moon. In this story, Kitty and her feline friends Pumpkin and Pixie discover a secret garden on a city rooftop, but as news of the garden spreads, not all that visit it choose to respect and care for the space. It's up to Kitty to save the garden and its beauty from those who seem intent on destroying it.